Pengaruh Tekanan Ketaatan, Pengetahuan Audit Dan Pengalaman Audit Terhadap Audit Judgement - Pinta Yunanico Pramuditha; Erinos NR (Universitas Negeri Padang, 2020)
This study aims to determine the effect of obedience pressure, audit knowledge and audit experience on audit judgment. This research was conducted in Inspektorat Provinsi Sumatera Barat.The respondents used in this study were 40 employees. Sample selection is done by using purposive sampling method. Data collection was carried out through a questionnaire. The analysis technique used in this study is Multiple Regression Analysis. The results of this study found that, obedience pressure, audit knowledge and audit experience have a positive effect on audit judgment